Negative plate and lithium ion secondary battery

By designing graphite negative electrode material layer and hybrid coating in the negative electrode sheet of lithium-ion battery, and using polymer particles to form stable bonds with the separator, the problems of short cycle life of lithium-ion battery cells and the negative electrode lithium analysis are solved, and high Energy density and long cycle life battery performance.

CN119419213AActive Publication Date: 2025-02-11SHENZHEN HAODYNE TECH CO LTD

Patent Information

Application Number
CN202510012724.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The cell cycle life of lithium-ion batteries is relatively short, especially when the surface lithium-ion electrode plate is under high-speed charging, which cannot meet the needs of industry applications.

Method used

By designing the graphite negative electrode material layer and a hybrid coating in the negative electrode sheet, polymer particles are used to form stable bonds with the separator during hot pressing, improving the cell cycle life and charging performance.

Benefits of technology

It effectively improves the cell cycle life of lithium-ion batteries by more than 20%, and the capacity retention rate of 1,000-week cycle in room temperature is above 93%, avoiding the lithium-ion problem of negative electrode plate under large-scale fast charging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419213A_ABST
    Figure CN119419213A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode plate. The negative electrode plate comprises a negative electrode current collector, a graphite negative electrode material layer positioned on the surface of the negative electrode current collector, and a mixed coating of graphite and polymer particles positioned on the surface of the graphite negative electrode material layer, the graphite negative electrode material layer comprises graphite, the mixed coating comprises graphite and polymer particles, and the average particle size D1 of the graphite in the graphite negative electrode material layer and the average particle size D3 of the polymer particles are both larger than the average particle size D2 of the graphite in the mixed coating. The glass transition temperature Tg of the polymer particles is 60 DEG C or below, the polymer modulus is 250-400 MPa, and the swelling degree in an electrolyte is 10-30%. The negative plate provided by the invention can form stable bonding with the diaphragm in the hot pressing process, and the bonding force is improved by more than one time; when the negative plate is applied to the lithium ion secondary battery, the cycle life of a battery cell can be effectively prolonged by more than 20%, and lithium is not separated out during charging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to a negative electrode sheet and a lithium ion secondary battery using the negative electrode sheet. Background Art

[0002] As a secondary battery, lithium-ion batteries have outstanding advantages such as high energy density, high output power density, long cycle life, extremely low self-discharge rate, wide temperature adaptability range, and short charging time. Lithium-ion batteries have not only successfully replaced lead-acid batteries in the field of power batteries, but also played an important role in the fields of national defense, military, and aerospace. They are also gradually replacing nickel-hydrogen and lead-acid batteries to achieve iterative upgrades of equipment. At the same time, people's performance requirements for lithium-ion batteries have also been further improved, requiring lithium-ion batteries to have high energy density and long cycle life.

[0003] Due to poor contact at the cell interface, the electrolyte is consumed too quickly during the cycle, resulting in too fast cycle decay, and the cell cycle life of lithium-ion batteries is short. Moreover, lithium is deposited on the surface of the negative electrode under high-rate fast charging, which cannot meet the application needs of the industry.

[0004] In order to solve this problem, the current industry mainly uses the method of coating the diaphragm with glue to bond the diaphragm and the electrode together to improve the interface performance. However, this method will have the problem of insufficient bonding between the diaphragm glue layer and the negative electrode sheet and poor bonding. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a negative electrode sheet and a lithium ion secondary battery. The negative electrode sheet can form a stable bond with the separator during the hot pressing process, and the cycle life of the lithium ion battery cell is effectively improved, and no lithium is deposited during charging.

[0006] The present invention achieves the technical effects through the following technical solutions: In a first aspect, the present invention provides a negative electrode sheet, comprising a negative electrode current collector, a graphite negative electrode material layer located on the surface of the negative electrode current collector, and a mixed coating of graphite and polymer particles located on the surface of the graphite negative electrode material layer; the graphite negative electrode material layer contains graphite, the mixed coating contains graphite and polymer particles that act as a bond with a diaphragm, and the average particle size D1 of the graphite in the graphite negative electrode material layer and the average particle size D3 of the polymer particles are both greater than the average particle size D2 of the graphite in the mixed coating.

[0007] The polymer particles also need to meet the requirements of glass transition temperature, modulus and swelling degree at the same time. The glass transition temperature Tg of the polymer particles is below 60°C, preferably -60~ -10°C. Specifically, it can be -20°C, -30°C, -40°C, -42°C, -45°C, -48°C, -50°C, -52°C, -55°C, -60°C, etc. The polymer modulus is 250~400MPa, specifically, it can be 250MPa, 260MPa, 280MPa, 300MPa, 320MPa, 350MPa, 365MPa, 372MPa, 381MPa, 400MPa, etc.; preferably, the polymer modulus is 260~360MPa, and the best is 300MPa. The swelling degree of the polymer particles in the electrolyte is 10-30%, specifically, it can be 10%, 12%, 14%, 17%, 20%, 23%, 26%, 30%, etc.; preferably, the swelling degree of the polymer particles in the electrolyte is 12-25%, and the best is 15%.

[0008] In the present invention, the average particle size D1 of the graphite in the graphite negative electrode material layer is 8-20 μm, specifically, it can be 8 μm, 9 μm, 12 μm, 15 μm, 17 μm or 20 μm, etc.; preferably, D1 is 13-16 μm, and the best is 15 μm. The average particle size D2 of the graphite in the mixed coating is 3-7 μm, specifically, it can be 3 μm, 3.5 μm, 5.5 μm, 6 μm or 7 μm, etc.; preferably, D2 is 4-6 μm, and the best is 5 μm. The average particle size D3 of the polymer particles is 10-15 μm, specifically, it can be 10 μm, 11 μm, 12.5 μm, 14 μm or 15 μm, etc.; preferably, D3 is 12-14 μm.

[0009] The graphite in the graphite negative electrode material layer is natural graphite or artificial graphite, preferably natural graphite, and the graphite in the mixed coating is artificial graphite.

[0010] Preferably, the thickness of the graphite negative electrode material layer is 60-90% of the total thickness of the negative electrode sheet, and the ratio of the thickness of the graphite negative electrode material layer to the thickness of the mixed coating is 3-5:1.

[0011] More preferably, the thickness of the graphite negative electrode material layer is 80-120 μm, specifically, 80 μm, 90 μm, 100 μm, 105 μm, 110 μm, 116 μm, 120 μm, etc. The thickness of the mixed coating is 18-30 μm, specifically, 18 μm, 20 μm, 22 μm, 25 μm, 27 μm, 30 μm, etc.

[0012] In the technical solution of the present invention, preferably, the graphite negative electrode material layer and the mixed coating also contain a conductive agent and a binder, the conductive agent is selected from at least one of conductive carbon black SP and carbon nanotubes CNT, preferably conductive carbon black SP; the binder is selected from at least two of carboxymethyl cellulose CMC, polyacrylic acid PAA, and styrene-butadiene rubber SBR, preferably a mixture of the two, and the weight ratio is 1:1.

[0013] Preferably, in the graphite negative electrode material layer, the weight ratio of the graphite, the conductive agent, and the binder is (95-97): (0.5-2): (2-4). Specifically, it can be (95:2:3), (95.5:1.5:3), (96:2:2), (96.5:1:2.5), (97:1.5:1.5), etc.

[0014] Preferably, in the mixed coating, the weight ratio of the graphite, the conductive agent, the binder, and the polymer particles is (75-90): (0.5-2): (2-4): (5-20). Specifically, it can be (75:2:3:20), (80:2:2:16), (85:2:3:10), (88:1.5:3.5:7), (90:2:2:6), etc.

[0015] In a second aspect, the present invention further provides a lithium ion secondary battery, wherein the lithium ion secondary battery comprises the negative electrode sheet as described above.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The polymer particles contained in the mixed coating protrude from the surface of the negative electrode, and can form a stable bond with the separator during the hot pressing process. The bonding force is increased by more than 1 times compared with the existing separator-coated negative electrode sheet.

[0017] The negative electrode sheet is used in lithium-ion secondary batteries. The presence of polymer particles is conducive to increasing the battery's liquid retention and rate charging. The average particle size of the graphite in the mixed coating is small, and the small-particle graphite can make the rate charging performance better. It can effectively increase the battery cell cycle life by more than 20%, and the capacity retention rate of 1,000 cycles at room temperature is more than 93%. The prepared lithium-ion battery has the advantages of high energy density and good cycle performance. At the same time, it can avoid lithium precipitation on the surface of the negative electrode sheet under high-rate fast charging, meeting the application needs of the industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the structure of the negative electrode sheet of the present invention.

[0019] In the figure: 1-negative electrode current collector, 2-graphite negative electrode material layer, 3-mixed coating, 3.1-polymer particles. DETAILED DESCRIPTION

[0020] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In this specification, similar reference numerals represent similar items in the following drawings, and therefore, once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings.

[0021] In the description of the present invention, the term "average particle size" refers to the volume average particle size D of the particles. V 50.

[0022] The negative electrode sheet provided by the present invention is Figure 1 As shown, it includes a negative electrode current collector 1, a graphite negative electrode material layer 2 located on the surface of the negative electrode current collector 1, and a mixed coating 3 of graphite and polymer particles located on the surface of the graphite negative electrode material layer 2; the graphite negative electrode material layer 2 contains graphite, and the mixed coating 3 contains graphite and polymer particles 3.1 that act as a bond with the diaphragm.

[0023] In the present invention, the average particle size D1 of graphite in the graphite negative electrode material layer 2 is larger than the average particle size D2 of graphite in the mixed coating layer 3, which can achieve both graphite slurry performance and rate performance of the battery cell.

[0024] The average particle size D1 of the graphite in the graphite negative electrode material layer 2 is 8-20 μm, and the average particle size D2 of the graphite in the mixed coating 3 is 3-7 μm.

[0025] The graphite in the graphite negative electrode material layer 2 is natural graphite or artificial graphite, preferably natural graphite, which can have good adhesion with the current collector and reduce costs; the graphite in the mixed coating 3 is preferably artificial graphite, which can ensure the high-rate charging performance of the battery cell.

[0026] In the present invention, the polymer particles 3.1 are polymer particles of polyvinylidene fluoride PVDF or styrene butadiene rubber SBR. Its average particle size D3 is 10~15μm, which can not only ensure that the average particle size D3 of the polymer particles in the mixed coating 3 is greater than the average particle size D2 of the graphite in the mixed coating 3, but also ensure that the polymer particles 3.1 contained in the mixed coating 3 protrude 1~5μm from the surface layer. The preparation method of the polymer particles is not particularly limited, as long as the average particle size, glass transition temperature Tg, modulus and swelling requirements of the prepared polymer particles meet the required range. The glass transition temperature Tg of the polymer particles is below 60°C, the polymer modulus is 250~400MPa, and the swelling degree of the polymer particles in the electrolyte is 10~30%.

[0027] The polymer particles must meet the requirements of glass transition temperature, modulus and swelling at the same time. The glass transition temperature Tg of the polymer particles is preferably -60~ -10°C, which can ensure that the negative electrode sheet and the separator form a bond under normal production hot pressing conditions (85°C); the polymer modulus is 260~360MPa, and the best is 300MPa, which ensures the integrity of the polymer particles after hot pressing, avoids the particles from collapsing into the graphite negative electrode material layer after hot pressing, and is conducive to the penetration of the electrolyte into the battery cell; the swelling degree of the polymer particles in the electrolyte is 12~25%, and the best is 15%, which ensures the structural integrity and polymer particle bonding after liquid absorption.

[0028] The polymer particles that meet the requirements of the present application can be obtained commercially. The glass transition temperature of the polymer particles can be selected when purchased, or can be tested by oneself, for example, by using a differential scanning calorimeter (DSC).

[0029] The test method of the modulus of a polymer may also be known to those skilled in the art, for example: After the polymer particles are dissolved, they are placed in a PTFE mold with a length*width*thickness of 10cm*1cm*0.01cm. After being placed in a cool and dry place at room temperature for 2 to 3 days, they are transferred to a 60℃ forced air oven and dried for 8 hours to form a film, which is then tested in a universal stretching machine.

[0030] Test conditions: Test speed: 200mm / min, gauge length: 25.00mm, test temperature 25℃, test humidity: 49%.

[0031] The test method of the swelling degree of a polymer is well known to those skilled in the art, for example: Bake the sample at 120℃ for 2h, put the sample into a test bottle, pour in the electrolyte (composition EC:EMC:DEC=3:2:5, LiPF6 concentration 1mol / L), the electrolyte volume should be no less than 15 times the volume of the test sample, put the test bottle into a 70℃ oven and heat continuously for 72h.

[0032] Swelling degree = mass of sample after immersion / mass of sample before immersion In the present invention, preferably, the thickness of the graphite negative electrode material layer 2 is 60-90% of the total thickness of the negative electrode sheet, and the thickness ratio of the graphite negative electrode material layer 2 to the mixed coating 3 is 3-5:1. More preferably, the thickness of the graphite negative electrode material layer 2 is 80-120 μm, and the thickness of the mixed coating 3 is 18-30 μm. In this way, the amount of polymer particles can be reduced while ensuring the bonding between the electrode sheet and the diaphragm and improving the absorption rate of the winding core to the electrolyte, thereby ensuring the high energy density requirements of the battery.

[0033] In the present invention, preferably, the graphite negative electrode material layer 2 and the mixed coating 3 also contain a conductive agent and a binder, the conductive agent is selected from at least one of conductive carbon black SP and carbon nanotubes CNT, preferably conductive carbon black SP; the binder is selected from at least two of carboxymethyl cellulose CMC, polyacrylic acid PAA, and styrene butadiene rubber SBR, preferably a mixture of methyl cellulose CMC and styrene butadiene rubber SBR, and the weight ratio thereof is 1:1.

[0034] In the present invention, preferably, in the graphite negative electrode material layer 2, the weight ratio of the graphite, the conductive agent, and the binder is (95-97): (0.5-2): (2-4). In the mixed coating 3, the weight ratio of the graphite, the conductive agent, the binder, and the polymer particles is (75-90): (0.5-2): (2-4): (5-20). In this way, the content of the polymer particles is 5% to 20% of the weight of the mixed coating, and the battery performance is optimal.

[0035] In a second aspect, the present invention provides a lithium-ion secondary battery, comprising the negative electrode sheet as described above.

[0036] The present invention is further described below by way of examples. Unless otherwise specified, the reagents, materials and instruments used in the following description are all conventional reagents, conventional materials and conventional instruments, which are all commercially available, and the reagents involved can also be synthesized by conventional synthesis methods. For example, conductive carbon black SP comes from TIMCAL, Switzerland, styrene-butadiene rubber SBR comes from SBR AWG101 of Haodian Technology Co., Ltd., and methyl cellulose CMC comes from Weiyi CMC2300. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art.

[0037] Embodiment 1: (1) Preparation method of negative electrode sheet: Slurry of graphite negative electrode material layer: natural graphite, conductive agent and binder are mixed and dispersed uniformly in a weight ratio of 95:2:3 (this ratio is the dry material weight ratio) with deionized water to form a slurry, and the solid content of the slurry is 50wt%; wherein the average particle size D1 of natural graphite is 15μm, the conductive agent is conductive carbon black SP, and the binder is a mixture of SBR and CMC in a weight ratio of 1:1; Slurry of mixed coating: artificial graphite, conductive agent, binder and polymer particles are mixed and dispersed uniformly in a weight ratio of 75:2:3:20 (this ratio is the dry material weight ratio) with deionized water to form a slurry with a solid content of 50wt%; wherein, the average particle size D2 of artificial graphite is 5μm, the conductive agent is conductive carbon black SP, the binder is a mixture of SBR and CMC in a weight ratio of 1:1, the polymer particles are polyvinylidene fluoride PVDF, the average particle size D3 of which is 10μm, the glass transition temperature Tg is -35°C, the polymer modulus is 300MPa, and the swelling degree of the polymer particles in the electrolyte is 15%.

[0038] Coating: Double-layer co-extrusion coating method is used to coat the slurry of graphite negative electrode material layer and mixed coating layer at the same time, such as Figure 1 As shown, the graphite negative electrode material layer 2 is coated on the surface of the negative electrode current collector 1, and the mixed coating 3 is coated on the surface of the graphite negative electrode material layer 2. The thickness of the graphite negative electrode material layer 2 is 90 μm, and the thickness of the mixed coating 3 is 30 μm.

[0039] (2) Preparation of lithium-ion secondary batteries: The positive electrode sheet, separator and electrolyte of the lithium ion battery prepared according to the conventional method in the art and the negative electrode sheet prepared by the present invention are assembled into a 2Ah soft-pack battery according to the general process for preparing lithium ion batteries.

[0040] Example 2 The negative electrode sheet and preparation method thereof and the lithium ion battery provided in this embodiment are different from those in Embodiment 1 in that: The weight ratio of natural graphite, conductive agent and binder in the slurry of the graphite negative electrode material layer is 96:2:2; the average particle size D1 of natural graphite is 12 μm, the conductive agent is carbon nanotube CNT, and the binder is a mixture of PAA and CMC in a weight ratio of 1:1; The weight ratio of artificial graphite, conductive agent, binder and polymer particles in the slurry of the mixed coating is 80:2:2:16; the average particle size D2 of artificial graphite is 4μm, the conductive agent is carbon nanotubes CNT, the binder is a mixture of PAA and CMC in a weight ratio of 1:1, the polymer particles are SBR, the average particle size D3 is 12μm, the glass transition temperature Tg is -40°C, the polymer modulus is 320MPa, and the swelling degree of the polymer particles in the electrolyte is 13%.

[0041] The thickness of the graphite negative electrode material layer 2 is 100 μm, and the thickness of the mixed coating layer 3 is 20 μm.

[0042] Other conditions are the same as those in Example 1.

[0043] Example 3 The negative electrode sheet and preparation method thereof and the lithium ion battery provided in this embodiment are different from those in Embodiment 1 in that: The weight ratio of natural graphite, conductive agent and binder in the slurry of the graphite negative electrode material layer is 97:1.5:1.5; the average particle size D1 of natural graphite is 20 μm, the conductive agent is carbon nanotube CNT, and the binder is a mixture of PAA and SBR in a weight ratio of 1:1; The weight ratio of artificial graphite, conductive agent, binder and polymer particles in the slurry of the mixed coating is 90:2:2:6; the average particle size D2 of artificial graphite is 7μm, the conductive agent is carbon nanotubes CNT, the binder is a mixture of PAA and SBR in a weight ratio of 1:1, the polymer particles are PVDF, the average particle size D3 is 15μm, the glass transition temperature Tg is -35°C, the polymer modulus is 360MPa, and the swelling degree of the polymer particles in the electrolyte is 12%.

[0044] The thickness of the graphite negative electrode material layer 2 is 120 μm, and the thickness of the mixed coating layer 3 is 30 μm.

[0045] Other conditions are the same as those in Example 1.

[0046] Example 4 The difference between the negative electrode sheet and its preparation method and the lithium ion battery provided in this embodiment and the embodiment 1 is that the average particle size D1 of natural graphite in the graphite negative electrode material layer is 10 μm, the average particle size D2 of artificial graphite in the mixed coating is 3 μm, the average particle size D3 of polymer particles is 15 μm, the glass transition temperature Tg is -35°C, the polymer modulus is 280 MPa, and the swelling degree of polymer particles in the electrolyte is 20%. The thickness of the graphite negative electrode material layer 2 is 100 μm, and the thickness of the mixed coating 3 is 20 μm.

[0047] Other conditions are the same as those in Example 1.

[0048] Example 5 The difference between the negative electrode sheet and its preparation method and the lithium ion battery provided in this embodiment and the embodiment 1 is that the average particle size D1 of the natural graphite in the graphite negative electrode material layer is 8 μm, the average particle size D2 of the artificial graphite in the mixed coating is 4 μm, the polymer particles are SBR, the average particle size D3 is 11 μm, the glass transition temperature Tg is -40°C, the polymer modulus is 260 MPa, and the swelling degree of the polymer particles in the electrolyte is 28.5%. The thickness of the graphite negative electrode material layer 2 is 110 μm, and the thickness of the mixed coating 3 is 25 μm.

[0049] Other conditions are the same as those in Example 1.

[0050] Example 6 The difference between the negative electrode sheet and its preparation method and the lithium ion battery provided in this embodiment and the embodiment 1 is that the average particle size D1 of natural graphite in the graphite negative electrode material layer is 18 μm, the average particle size D2 of artificial graphite in the mixed coating is 6 μm, the average particle size D3 of polymer particles is 13 μm, the glass transition temperature Tg is -35°C, the polymer modulus is 375 MPa, and the swelling degree of polymer particles in the electrolyte is 11%. The thickness of the graphite negative electrode material layer 2 is 105 μm, and the thickness of the mixed coating 3 is 25 μm.

[0051] Other conditions are the same as those in Example 1.

[0052] Example 7 The difference between the negative electrode sheet and its preparation method and the lithium ion battery provided in this embodiment and the embodiment 1 is that the average particle size D1 of the natural graphite in the graphite negative electrode material layer is 20 μm, the average particle size D2 of the artificial graphite in the mixed coating is 3 μm, the average particle size D3 of the polymer particles is 10 μm, the glass transition temperature Tg is -35°C, the polymer modulus is 390 MPa, and the swelling degree of the polymer particles in the electrolyte is 10.5%. The thickness of the graphite negative electrode material layer 2 is 80 μm, and the thickness of the mixed coating 3 is 18 μm.

[0053] Other conditions are the same as those in Example 1.

[0054] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, although the coating of the negative electrode sheet has two layers, the outer layer slurry does not contain polymer particles.

[0055] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, although the coating of the negative electrode sheet has two layers, the average particle size D1 of the graphite in the two layers is equal to D2.

[0056] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that in this comparative example, although the coating of the negative electrode sheet has two layers, the average particle size D1 of the graphite in the two layers is smaller than D2.

[0057] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that in this comparative example, the average particle size D3 of the polymer particles in the mixed coating is smaller than the average particle size D2 of the graphite in the layer.

[0058] Comparative Example 5: The difference between Comparative Example 5 and Example 1 is that in this comparative example, the polymer particles of the mixed coating slurry are polymethyl methacrylate PMMA, whose glass transition temperature Tg is 105° C., the polymer modulus is 450 MPa, and the swelling degree of the polymer particles in the electrolyte is 8%.

[0059] Comparative Example 6: The difference between Comparative Example 6 and Example 1 is that in this comparative example, the polymer particles of the mixed coating slurry are polymethyl methacrylate PMMA, the glass transition temperature Tg is 105° C., the polymer modulus is 235 MPa, and the swelling degree of the polymer particles in the electrolyte is 30%.

[0060] Comparative Example 7: The difference between Comparative Example 7 and Example 1 is that in this comparative example, the polymer particles of the mixed coating slurry are polymethyl methacrylate PMMA, whose glass transition temperature Tg is 105° C., the polymer modulus is 400 MPa, and the swelling degree of the polymer particles in the electrolyte is 10%.

[0061] Comparative Example 8: The difference between Comparative Example 8 and Example 1 is that in this comparative example, the polymer particles of the mixed coating slurry are polymethyl methacrylate PMMA, whose glass transition temperature Tg is 105° C., the polymer modulus is 395 MPa, and the swelling degree of the polymer particles in the electrolyte is 9%.

[0062] Performance Test: The negative electrode sheets and 2Ah soft-pack batteries obtained in the above examples and comparative examples were subjected to performance tests, and the performance test results are shown in Table 1. [Capacity retention rate after 1000 cycles at room temperature] At 25°C, charge to 4.50V at a constant current of 1C, charge to 4.50V at a constant voltage of 0.05C, and then discharge to 3.0V at a discharge rate of 1C. Repeat this charge and discharge cycle 1000 times, and measure the discharge capacity at the first cycle and the discharge capacity at the 1000th cycle. Calculate the capacity retention rate Q after 1000 cycles according to the following formula: Capacity retention rate Q = Q1000 / Q1*100%.

[0063]

Battery fluid capacity

[0064] [Negative electrode lithium deposition test]: At 25°C, charge at a constant current of 2.5C to 4.35V, then charge at a constant voltage of 4.35V, with a cut-off current of 0.05C, and then discharge at a constant current of 1C, with a cut-off voltage of 2.75V. This is a charge and discharge cycle, and repeat the charge and discharge cycle 10 times. After the end, fully charge the battery at room temperature, disassemble the battery cell in a dry room environment, and observe the lithium deposition on the negative electrode surface. The degree of lithium deposition is divided into no lithium deposition, slight lithium deposition, moderate lithium deposition, and severe lithium deposition test results as shown in Table 1. Slight lithium deposition means that the lithium deposition area on the negative electrode surface is less than 1 / 10 of the overall area, and severe lithium deposition means that the lithium deposition area on the negative electrode surface exceeds 1 / 3 of the overall area.

[0065] [Adhesion between negative electrode sheet and separator] The negative electrode sheet and the diaphragm are hot pressed at 85°C and 1MPa. The adhesion between the diaphragm and the electrode sheet is tested after liquid injection. A universal tensile testing machine is used for peeling test. A 180° peeling method is used to fix the negative electrode sheet, and the diaphragm is pulled by the active end of the tensile testing machine to peel off the diaphragm and the negative electrode sheet.

[0066] Table 1 Performance test results of the electrodes and batteries corresponding to the embodiments and comparative examples

[0067] It can be seen from the performance test results in Table 1 that the negative electrode sheet provided by the present invention and the battery prepared by the negative electrode sheet can effectively improve the bonding strength with the separator and the performance of the battery. When polymer particles are added to the coating of the negative electrode sheet, when the average particle size of graphite, the average particle size of polymer particles, the glass transition temperature, the modulus and the swelling requirements are not within the range disclosed in the present invention, the bonding strength between the negative electrode sheet and the separator and the performance of the battery are reduced to varying degrees.

[0068] Specifically, by comparing the test results of Examples 1 to 7 with Comparative Example 1, it can be seen that if no polymer particles are added to the outer coating, the bonding strength between the diaphragm and the electrode will be significantly reduced, and the battery will suffer from severe lithium deposition during 4C charging, and the liquid retention capacity of the battery cell and the capacity retention rate after 1000 cycles at room temperature will be significantly reduced.

[0069] From the test results of Comparative Examples 1 to 7 and Comparative Examples 2 to 3, it can be seen that if the average particle size of graphite is not within the range disclosed in the present invention, the bonding strength between the diaphragm and the electrode will be significantly reduced, and the liquid retention of the battery cell and the capacity retention rate after 1000 cycles at room temperature will be significantly reduced.

[0070] From the test results of Comparative Example 1-Example 7 and Comparative Example 4, it can be seen that if the average particle size of the polymer particles in the mixed coating slurry is smaller than the average particle size of the graphite in this layer, the bonding strength between the diaphragm and the electrode will be significantly reduced, and the liquid retention amount of the battery cell and the capacity retention rate after 1000 cycles at room temperature will be significantly reduced.

[0071] It can be seen from the test results of Example 1 to Example 7 and Comparative Example 5 that if the glass transition temperature, modulus and swelling requirements of the polymer particles of the mixed coating slurry are not within the scope disclosed in the present invention, the bonding strength between the diaphragm and the electrode will be significantly reduced, and the battery will have slight lithium deposition during 4C charging, and the liquid retention capacity of the battery cell and the capacity retention rate after 1000 cycles at room temperature will be significantly reduced.

[0072] From the test results of Comparative Examples 1 to 7 and Comparative Examples 6 to 8, it can be seen that if at least one of the three parameters of the glass transition temperature, modulus and swelling degree of the polymer particles of the mixed coating slurry is not within the range disclosed in the present invention, the bonding strength between the diaphragm and the electrode will be significantly reduced, and the battery will have slight lithium deposition during 4C charging, and the liquid retention capacity of the battery cell and the capacity retention rate after 1000 cycles at room temperature will be significantly reduced.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A negative electrode sheet, characterized in that: It includes a negative electrode current collector, a graphite negative electrode material layer located on the surface of the negative electrode current collector, and a mixed coating of graphite and polymer particles located on the surface of the graphite negative electrode material layer; the graphite negative electrode material layer contains graphite, the mixed coating contains graphite and polymer particles, the average particle size D1 of the graphite in the graphite negative electrode material layer and the average particle size D3 of the polymer particles are both larger than the average particle size D2 of the graphite in the mixed coating, the glass transition temperature Tg of the polymer particles is below 60°C, the polymer modulus is 250~400MPa, and the swelling degree of the polymer particles in the electrolyte is 10~30%.

2. The negative electrode sheet according to claim 1, characterized in that: The average particle size D1 of the graphite in the graphite negative electrode material layer is 8-20 μm, the average particle size D2 of the graphite in the mixed coating is 3-7 μm, and the average particle size D3 of the polymer particles is 10-15 μm.

3. The negative electrode sheet according to claim 1 or 2, characterized in that: The graphite in the graphite negative electrode material layer is natural graphite or artificial graphite, and the graphite in the mixed coating is artificial graphite.

4. The negative electrode sheet according to claim 1 or 2, characterized in that: The glass transition temperature Tg of the polymer particles is -60 to -10°C.

5. The negative electrode sheet according to claim 1, characterized in that: The thickness of the graphite negative electrode material layer is 60-90% of the total thickness of the negative electrode sheet, and the ratio of the thickness of the graphite negative electrode material layer to the thickness of the mixed coating is 3-5:

1.

6. The negative electrode sheet according to claim 5, characterized in that: The thickness of the graphite negative electrode material layer is 80-120 μm, and the thickness of the mixed coating is 18-30 μm.

7. The negative electrode sheet according to claim 1, characterized in that: The graphite negative electrode material layer and the mixed coating layer also contain a conductive agent and a binder. The conductive agent is selected from at least one of conductive carbon black SP and carbon nanotubes; the binder is selected from at least two of carboxymethyl cellulose, polyacrylic acid, and styrene-butadiene rubber.

8. The negative electrode sheet according to claim 7, characterized in that: In the graphite negative electrode material layer, the weight ratio of the graphite, the conductive agent, and the binder is (95-97): (0.5-2): (2-4).

9. The negative electrode sheet according to claim 7, characterized in that: In the mixed coating, the weight ratio of the graphite, the conductive agent, the binder, and the polymer particles is (75-90): (0.5-2): (2-4): (5-20).

10. A lithium ion secondary battery, characterized in that: A negative electrode sheet comprising any one of claims 1 to 9.

Citation Information

Patent Citations

  • Negative electrode for secondary battery and secondary battery comprising same

    CN114430021A

  • Negative pole piece, preparation method thereof and secondary battery

    CN114927639A

  • Electrode plate, electrochemical device and electronic device

    CN115606015A

  • Lithium ion secondary battery negative electrode slurry composition, a lithium ion secondary battery negative electrode, and lithium ion secondary battery

    US20120295159A1

  • Electrode for lithium battery, lithium battery including the same, and method of manufacturing the lithium battery

    US20180108914A1

Cited By

  • Negative pole piece and secondary battery

    CN120914198A

  • Method for manufacturing a battery cell, as well as a battery cell

    DE102025105517B3